A study on the pig rearing industry with regards to pollution laws in Malaysia / Ahmad Maududi Mahdi, Zulkifli Awang and Elyazura Md Shaarani @ Md Nawi - Mahdi, Ahmad Maududi; Awang, Zulkifli; Md Shaarani @ Md Nawi, Elyazura (2007)
Human activities have led the world into a serious problem which is global warming and clearly the increasing rate of environmental pollution in various forms does contribute as a factor to this problem. Many people are liable for their action but the most active polluter are developers involved in different kind of industry. One of them is the pig rearing industry. Reported cases of lacking efficiency in treating pig waste and water treatment had made the water supply of the neighbour and our nation's river as the victim. History of the nation in 1999 showed that Malaysia has experienced a major disease outbreak known as Japanese Encephalitis and undoubtedly the course of action would be contaminating water due to poor treatment of the waste. Pollution caused by this people still in exist though the government had set up guidelines and laws regulating this matter. Could it be the enforcement factor that lacking in the public authority or the laws themselves are weak and insufficient. Such issues must be determined and re-construct in order for the government to achieve better environmental quality for the nation.